The Influence of Total Quality Management on Physical Facility Development in Sukabumi Area Shoe Company - Danang Purwanto; Dio Damas Permadi; Novita Aprilia; Matrunevich Oksana Viktorovna (Nusa Putra University, 2023)
A manufacturing company is a type of company that produces finished goods and sells them. The development of physical facilities has a role in facilitating and expediting the company before a business activity takes place. The development of physical facilities also needs to pay attention to the construction of physical facilities as well as the K3 (Occupational Health and Safety) aspect where the company upholds the value that employees are the company's most important asset. This study aims to analyze the effect of implementing TQM on the development of physical facilities using a quantitative descriptive method. The results of this study indicate that TQM has an effect of 19.6% on the development of these physical facilities, so that the implementation of a good TQM system can improve the quality of work as well as the quality of the resulting buildings.